The Power of the Pump: Windmills in the Flint Hills - Christy Davis (Symphony in the Flint Hills, 2018)
Introduction: Before the 1850s in America, windmills were merely metaphors for the quixotic. This changed in 1854 with the invention of the first commercially viable windmill, a so-called self-governing model that automatically turned to face the shifting wind.